2021
DOI: 10.3389/fphar.2021.764885
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Kratom Opioid Derivatives as Potential Treatment Option for Alcohol Use Disorder

Abstract: Background and Purpose:Mitragyna speciosa extract and kratom alkaloids decrease alcohol consumption in mice at least in part through actions at the δ-opioid receptor (δOR). However, the most potent opioidergic kratom alkaloid, 7-hydroxymitragynine, exhibits rewarding properties and hyperlocomotion presumably due to preferred affinity for the mu opioid receptor (µOR). We hypothesized that opioidergic kratom alkaloids like paynantheine and speciogynine with reduced µOR potency could provide a starting point for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 79 publications
1
13
0
1
Order By: Relevance
“…However, a recent analysis by Buckhalter et al demonstrated that "Rifat" kratom (purchased from the same supplier as K55 and K59) does exhibit antidepressant-like and analgesic effects [43]. This activity may be from the two major constituents, 13 and 3-isoajmalicine, or may be attributed to metabolism products, as has been shown with 7-hydroxyspeciogynine [44] and 9-O-desmethylspeciogynine (i.e., gambirine) [45]. Further experiments would be needed to verify any predictions of biological activity based on differences in alkaloid content.…”
Section: Sample Isomitraphyllinementioning
confidence: 98%
“…However, a recent analysis by Buckhalter et al demonstrated that "Rifat" kratom (purchased from the same supplier as K55 and K59) does exhibit antidepressant-like and analgesic effects [43]. This activity may be from the two major constituents, 13 and 3-isoajmalicine, or may be attributed to metabolism products, as has been shown with 7-hydroxyspeciogynine [44] and 9-O-desmethylspeciogynine (i.e., gambirine) [45]. Further experiments would be needed to verify any predictions of biological activity based on differences in alkaloid content.…”
Section: Sample Isomitraphyllinementioning
confidence: 98%
“…The endogenous agonists for the δOR are pentapeptide enkephalins, particularly Leu 5 -enkephalin, but other peptides that originate from plants and other species, like frogs can also bind and activate the δOR [ 1 , 2 ]. Similar to the µ opioid receptor (µOR), which is activated by small molecules from natural products like opium and kratom and fully synthetic small molecules like fentanyl, the δOR can be activated by a variety of naturally occurring and (semi-) synthetic small molecules [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Front and center have been the ability of δOR selective agonists to reduce chronic pain, be it inflammatory, neuropathic, or migraine [ 7 ]. δOR agonists have shown promise in preventing cardiac and cerebral ischemia [ 8 ], as a potential treatment for neurodegenerative diseases [ 9 , 10 , 11 , 12 , 13 ], and both δOR agonists and antagonists have been proposed as mechanisms for the treatment of alcohol use disorder [ 5 , 14 , 15 , 16 ]. Outside the central nervous system, δOR antagonism and positive allosteric modulation of δOR has been proposed as a treatment for gastrointestinal motility disorders, such as irritable bowel syndrome [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The δ-opioid receptor (δOR) is a G-protein coupled receptor (GPCR) within the opioid family that has been considered as therapeutic target for the treatment of migraine, chronic pain, anxiety, and major depressive disorder ( Jutkiewicz, 2006 ; Perrine et al, 2006 ; Pradhan et al, 2011 ; Pradhan et al, 2014 ; Gendron et al, 2016 ; Cahill et al, 2022 ). δOR agonists have also been proposed as promising treatments for alcohol use disorder, ischemia, and stroke ( Schultz et al, 1997 ; Karck et al, 2001 ; Alongkronrusmee et al, 2018 ; Grant Liska et al, 2018 ; Sheng et al, 2018 ); particularly as δOR agonists generally display negligible abuse potential ( Van Rijn et al, 2012 ; Hudzik et al, 2014 ; Conibear et al, 2020 ; Gutridge et al, 2021 ) and thus, would be safer alternatives relative to µ-opioid receptor drugs. Yet, in contrast to the µ-opioid and κ-opioid receptor, no δOR selective compounds have been approved for clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of SNC80 to induce seizures is absent in δOR knockout mice, indicating an on-target effect ( Broom et al, 2002b ; Chung et al, 2015 ). Yet, multiple δOR selective agonists have been designed and characterized to specifically lack this seizurogenic effect ( Saitoh et al, 2011 ; Saitoh et al, 2018 ; Conibear et al, 2020 ; Fossler et al, 2020 ; Gutridge et al, 2021 ). These findings hint at a concept of biased signaling, where a particular ligand activates a subset of signal-transduction pathways thereby promoting or avoiding specific cellular signaling and associated physiological consequences.…”
Section: Introductionmentioning
confidence: 99%